Liquefaction of palm kernel shell to bio-oil using sub- and supercritical water: An overall kinetic study. Issue 3 (June 2019) - Chan, Yi Herng; Quitain, Armando T.; Yusup, Suzana; Uemura, Yoshimitsu; Sasaki, Mitsuru; Kida, Tetsuya
Abstract: Palm kernel shell was liquefied using sub- and supercritical water at 330–390 °C and 25 MPa for different reaction times. The overall kinetics of the liquefaction based on the conversion of biomass was analyzed using kinetic equation adopted from the literature, and the kinetic parameters were estimated from the evaluation of the kinetic equation. In this study, the rate constant (k) increased from 0.43 to 0.49 s −1 with reaction temperature from 330 to 390 °C. The relationship of rate constant (k) and temperature agreed reasonably well with the Arrhenius equation. The activation energy (E) and pre-exponential factor (A) values for the liquefaction process were estimated to be 6.70 kJ/mol and 1.65 s −1, respectively. In addition, the experimental bio-oil yields with respect to reaction time were well-fitted using the modified Reverchon-Sesti Osseo equation. Highlights: Palm kernel shell was liquefied using sub- and supercritical water. Kinetic analysis and modelling of liquefaction of palm kernel shell was performed. Relationship of rate constant and temperature was evaluated based on Arrhenius law. Bio-oil yields were well-fitted using the modified Reverchon-Sesti Osseo model.